Roadmap to Baku - (:unkn) unknown (My University, 2024)
This report outlines Africa’s strategic priorities and diplomatic positioning in the lead-up to COP29 in Baku, emphasizing key climate negotiation themes such as climate finance, adaptation, loss and damage, and just energy transition. It provides an analytical review of COP28 outcomes, including the operationalization of the Loss and Damage Fund, the UAE Consensus on fossil fuels, and the Global Stocktake’s implications for Africa. The report highlights Africa’s vulnerabilities to climate change, particularly in the face of extreme weather events, climate-induced socioeconomic challenges, and inadequate financing mechanisms. As COP29 is expected to be a "finance COP," the document articulates Africa’s call for a new collective quantified goal (NCQG) that secures predictable, equitable, and concessional climate finance. Furthermore, it underscores the importance of Africa’s just energy transition, advocating for a balance between economic development and decarbonization efforts. This roadmap serves as a critical guide for African policymakers, negotiators, and civil society actors, ensuring that Africa’s climate agenda is effectively represented in global climate governance.
Keywords: African Research